Tensão e extensão: ensaio sobre a ontologia bergsoniana - Henriques, Fernando Meireles Monegalha (Universidade Federal de São Carlos, 2010)
In this work, our aim is to show how Bergson s consciousness analysis is linked to his ontology. For that, we will begin with an analysis of temporal dimensions that are implicit in the idea of duration. Then, we will approach the idea that Bergson thinks our consciousness as a temporal field within past, present and future are linked. From there, we will try to show that this temporal field acknowledges several levels, as he put forward by his degrees of duration s theory. Thereafter, we will be ready to display the internal link between temporality and ontology according to Bergson, insofar our consciousness will be, for the French philosopher, just one of varied levels composing real s internal structure, insomuch other degrees of duration can be thought being high or low from this average temporal degree that our subjectivity is. Low: minimal temporality of our own body and lowermost duration of the matter. High: the concretion of duration or eternity of life , which is going to be called God by Bergson. In all these cases, the point is to think in duration, that is, to think varied strata of real by their temporal features, defining their respective places in a sole temporal structure, that we can go through by our own being s immanent intuition, in a movemente which Bergson will assert to be the metaphysics itself . These varied degrees of duration, in turn, will reveal being in a reverse relation to the consciousness extension: the bigger the past contraction made by our consciousness, that is, the bigger its intensity, the lesser its extension in the world. We will attempt to show that this idea of a reverse relation between the duration degrees and extension ones permeates a large part of Bergson s work, and it is very helpful in order to make Bergson s work clearer. Finally, our aim is to show how Bergson thinks his ontology from a genetic point of view: for that, we will elucidate what the concept of vital impulse hides and we will understand what the singular procession presented by Bergson in the third chapter of Creative Evolution consists of.
Keywords: Ontologia; Espaço e tempo; Intuição; Metafísica; Filosofia francesa; Tempo (Filosofia); Graus de duração; Temporalidade; Matéria; Corpo; Duration degrees; Temporality; Ontology; Matter; Body; CIENCIAS HUMANAS::FILOSOFIA